Species composition, distribution, and biomass of meiofauna in the Visayam sea. - Mequila, Annie Trixie L.
Meibenthic composition of the Visayan sea was investigated from April 24-May 02, 2001. Core samples were taken from grab sample collected at 17 stations. Elutriation was employed to separate the organisms from the sediment. Organisms retined in 63 um sives were identified to lowest level possible., A total of 126 species comprising 25 major meiobenthic taxa were recorded. Overall mean density was 1,246,574.24 indiv./m squared and overall mean biomass was 0.11g/m squared. Nematodes and harpacticoid copepods dominated the samples and comprised 92.2% of the total abundance. Geographially, harpacticoids were abundant in sandy substrate while nematodes were widely distributed. Both meiofaunal density and biomass were negatively correlated with median sediment grain size and % mud, while a positive correlation was shown on % sand.